2004
DOI: 10.1080/07391102.2004.10506975
|View full text |Cite
|
Sign up to set email alerts
|

The Triplet Code From First Principles

Abstract: Temporal order ("chronology") of appearance of amino acids and their respective codons on evolutionary scene is reconstructed. A consensus chronology of amino acids is built on the basis of 60 different criteria each offering certain temporal order. After several steps of filtering the chronology vectors are averaged resulting in the consensus order: G, A, D, V, P, S, E, (L, T), R, (I, Q, N), H, K, C, F, Y, M, W. It reveals two important features: the amino acids synthesized in imitation experiments of S. Mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
263
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(282 citation statements)
references
References 55 publications
16
263
1
2
Order By: Relevance
“…These results suggest that Leu, Ile, His, and Lys may have once occupied the entire codon block, and specific codons were later conceded to the other amino acids. Specifically, the data provide evidence for the capture of AUG from Ile to Met, consistent with what is considered a key codon capture event (24,25), as well as unique evidence that Phe may have captured the UUY codons from Leu. Our data also suggest that a subset of codons of Lys and His were reassigned to Asn and Gln, respectively.…”
Section: Codons or Anticodons For Select Amino Acids Are Enriched Neamentioning
confidence: 68%
See 1 more Smart Citation
“…These results suggest that Leu, Ile, His, and Lys may have once occupied the entire codon block, and specific codons were later conceded to the other amino acids. Specifically, the data provide evidence for the capture of AUG from Ile to Met, consistent with what is considered a key codon capture event (24,25), as well as unique evidence that Phe may have captured the UUY codons from Leu. Our data also suggest that a subset of codons of Lys and His were reassigned to Asn and Gln, respectively.…”
Section: Codons or Anticodons For Select Amino Acids Are Enriched Neamentioning
confidence: 68%
“…Our finding on ribosomal anticodon-amino acid enrichment, when compared with the consensus chronology of amino acids built on 60 criteria (24), revealed a distinct stage for the evolution of the canonical code. Except for Asp, all other amino acids that are significantly enriched with their anticodons in the ribosome are at the later stage of amino acid expansion (Table 1), starting from Leu (ranked No.…”
Section: Codons or Anticodons For Select Amino Acids Are Enriched Neamentioning
confidence: 96%
“…Roughly speaking, the frequencies of G, A, D, V, P, L, T, R, H, W tend to decrease, the frequencies of S, E, I, N, K, F, Y tend to increase, and the frequencies of Q, C, M tend to keep constant. The magnitudes of variations are different: frequencies of G, A, V, P, R decrease more rapidly than that of D, L, T, H, W, while frequencies of I, N, K, F, Y increase more rapidly than that of S, E. We found that the evolutionary trends of amino acids are related to the amino acid chronology [13]: most of the amino acids whose frequencies tend to decrease (or increase) are among the earlier (or later) recruited amino acids according to the amino acid chronology. The variation trends of amino acid frequencies are intrinsic properties of molecular evolution, which are irrelative to the choice of orders in sorting species.…”
Section: General Variation Trends Of Amino Acid Frequenciesmentioning
confidence: 78%
“…The genetic code likely evolved from a primitive, smaller group of amino acids to the modern complement of 20 amino acids via a series of ambiguous intermediate codes (7,17). According to this hypothesis, each codon block would originally have included a greater number of codons that recursively cycled between ambiguity and specific coding, until eventually the modern codon assignments evolved.…”
mentioning
confidence: 99%
“…With the exception of phenylalanine, the NUN-encoded amino acids are structurally similar. (Phenylalanine may have "captured codons" from the NUN block, as a later addition to the genetic code [17].) Therefore, the cognate aminoacyl-tRNA synthetases would naturally be more permissive towards these related amino acids.…”
mentioning
confidence: 99%